Rehabilitation using single stage implants - Mohamed Jumshad; Sudarsan Sabitha; Arun K; Shivakumar B (Wolters Kluwer Medknow Publications, 2009)
Implant related prosthesis has become an integral part of rehabilitation of edentulous areas. Single stage implant placement has become popular because of its ease of use and fairly predictable results. In this paper, we present a series of cases of single stage implants being used to rehabilitate different clinical situations. All the implants placed have been successfully restored and followed up for up to one year.